Behavior modeling for product design support focusing on topological information of components - Itsuki HATANO; Eiji MORINAGA; Hidefumi WAKAMATSU (Nihon Kikai Gakkai ronbunshu, 2020)
In recent years, with globalization in industry, there is a concern about increase of defects caused by using products in unexpected ways. To solve this problem, a method to predict such defects in the products in advance in the design stage has been proposed, in which behaviors of the products and physical phenomena are represented by Petri net. However, in order to achieve a more accurate prediction, it is necessary to consider topological information of components of the products. In this research, we aimed to represent topological information of elements of an electric circuit, and to make it possible to detect defects in cooperation with the method of the previous research. By modeling each element in an electrical circuit by Petri net and connecting them each other following the connection state of the circuit, it is possible to build a model that represents topological information of the circuit. And, two types of the model can check whether there is a closed circuit and which element the current flows through. In addition, by integrating them and the conventional model and reflecting the information in the circuit to the conventional model, more accurate defect detection can be performed. The effectiveness of the method was shown by case studies using simple circuit examples.